2022
DOI: 10.3389/fimmu.2022.954007
|View full text |Cite
|
Sign up to set email alerts
|

Soluble markers of B cell activation suggest a role of B cells in the pathogenesis of systemic sclerosis-associated pulmonary arterial hypertension

Abstract: IntroductionSoluble markers of B cell activation are interesting diagnostic and prognostic tools in autoimmune diseases. Data in systemic sclerosis (SSc) are scarce and few studies focused on their association with disease characteristics.Methods1. Serum levels of 14 B cell biomarkers (β2-microglobulin, rheumatoid factor (RF), immunoglobulins (Ig) G, IgA, IgM, BAFF, APRIL, soluble (s)TACI, sBCMA sCD21, sCD23, sCD25, sCD27, CXCL13) were measured in SSc patients and healthy controls (HC). 2. Associations between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 102 publications
0
10
0
Order By: Relevance
“…Activated B cells in SSc promote endothelial cells and fibroblasts to secrete proinflammatory and fibrogenic factors, leading to vascular injury and fibrosis ( 53 ). Serum IgM is a soluble marker of B cell activation and one of the diagnostic markers of SSc ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated B cells in SSc promote endothelial cells and fibroblasts to secrete proinflammatory and fibrogenic factors, leading to vascular injury and fibrosis ( 53 ). Serum IgM is a soluble marker of B cell activation and one of the diagnostic markers of SSc ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activated B cells in SSc promote endothelial cells and fibroblasts to secrete proinflammatory and fibrogenic factors, leading to vascular injury and fibrosis ( 53 ). Serum IgM is a soluble marker of B cell activation and one of the diagnostic markers of SSc ( 53 ). In this study, we found that ENST00000313807 and hsa-miR-29b-3p in the plasma cirexos of patients with SSc were positively correlated with IgM.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the BAFF system in B-cell activation in the context of PAH has yet to be thoroughly investigated. Serum BAFF concentrations have been assessed in several SSc cohorts: while BAFF levels are similar in patients with and without pulmonary hypertension, they strongly correlate with clinical markers of pulmonary hypertension severity in SSc-PAH patients [ 42 45 ]. A pathogenic variant in the gene coding for TACI has been identified as a new causative mutation for PAH, possibly by promoting dysregulated vascular inflammation [ 46 ].…”
Section: Activating Mechanisms Of B-cells In Pahmentioning
confidence: 99%
“…Although not measured in this cohort, previous studies reported elevated IgE levels in iPAH patients, due to skewed isotype switching induced by Th2 cytokines [ 25 , 26 ]. Few data are available regarding patients with CTD-PAH, with conflicting reports of elevated IgA [ 64 ] and decreased IgG [ 45 ] levels in SSc-PAH (compared to SSc without pulmonary hypertension).…”
Section: Effector Mechanisms Of B-cells In Pahmentioning
confidence: 99%
“…Increased levels of the acute phase response protein pentraxin-3 (PTX3) were found in patients with PAH, especially CTD-PAH, vs. those of healthy controls and CTD patients without PAH, without any correlation with BNP or CRP levels, identifying PTX3 as an early marker of PAH, especially in CTDs [ 148 ]. Recently, soluble markers of B cell activation were found to be elevated in the serum of SSc patients; in particular, a correlation was shown between serum levels of B-cell activating factor (BAFF), NT-proBNP levels and forced vital capacity (FVC)/DLCO ratio in lcSSc-PAH patients, although, overall, serum BAFF levels were not significantly higher in SSc patients with PAH vs. those without PAH [ 149 ].…”
Section: Inflammationmentioning
confidence: 99%